Sharia Smart Card Strategy for Increasing Sharia Economic and Financial Literacy - Arif (International Journal of Strategic Studies, 2024)
Based on the results of the OJK survey 2022, the level of sharia financial literacy in Indonesia is still shallow, namely 9.14%. The low level of public literacy regarding Sharia finance is a fundamental problem that must be immediately resolved from its roots. This research aims to increase sharia economic and financial literacy for students in Indonesia based on a card game called SSD. The method used is Research and Development (RnD) and is reinforced with qualitative description. The research results show that there are 40 SSD cards with ten categories. Each category has four sub-categories that explain Sharia economics and finance. With techniques made to match, SSD makes classroom learning more accessible for students to understand because it uses a fun approach.